Factors Associated With Enhanced Availability of Zika Virus Testing Information on Health Department Websites [29K]. (May 2017) - Rivera, Joshua O.; Page-Ramsey, Sarah; Rodriguez, Emma; Menchaca, Ryan; Ireland, Kayla; Ramsey, Patrick
Abstract : INTRODUCTION: Our objective was to evaluate factors associated with increased Zika virus testing information on health department websites in the United States and its territories. METHODS: We reviewed each US state, District of Columbia, and territory (Puerto Rico, Guam, US Virgin Islands, American Samoa, North Marianas Islands) health department websites for information on Zika virus testing. Websites were grouped as either having Zika testing information or not. Factors potentially associated with the presence of testing information on websites were compared between groups, including birth rates, presence of the Aedes mosquito, presence of Zika cases in the state/territory, and designation as a border state/territory. RESULTS: 71% of 56 state/territory websites had Zika testing information. Mean birth rates were similar between those states with testing information and those without (12.2/1000 vs 13.8/1000, p=0.06). Websites with Zika testing information were more likely to be in areas with Aedes mosquitoes (92.5% vs 62.5%, p=0.01) and to have documented Zika cases (97.5% vs 68.8%, p=0.006) compared to those without information. Designation as a border state/territory did not impact likelihood of Zika testing information on the website (12.5% vs 25.0%, p=0.26). CONCLUSION: Zika testing information is more likely to found on state/territory websites where the Aedes mosquito is present and where Zika cases have occurred. Birth rate and border status do not impact the presence of Zika testing information on the state/territory website.